Cross-Species Complementation of Nonessential Yeast Genes Establishes Platforms for Testing Inhibitors of Human Proteins. Issue 3 (1st March 2020) - Hamza, Akil; Driessen, Maureen R M; Tammpere, Erik; O'Neil, Nigel J; Hieter, Philip
Abstract: Given the broad utility of humanized yeast to model and study human biology, a reference set of human genes that can replace cognate yeast genes and operate in yeast is needed. Hamza et al. present... Cross-species complementation can be used to generate humanized yeast, which is a valuable resource with which to model and study human biology. Humanized yeast can be used as an in vivo platform to screen for chemical inhibition of human protein drug targets. To this end, we report the systematic complementation of nonessential yeast genes implicated in chromosome instability (CIN) with their human homologs. We identified 20 human–yeast complementation pairs that are replaceable in 44 assays that test rescue of chemical sensitivity and/or CIN defects. We selected a human–yeast pair (h FEN1 /y RAD27 ), which is frequently overexpressed in cancer and is an anticancer therapeutic target, to perform in vivo inhibitor assays using a humanized yeast cell-based platform. In agreement with published in vitro assays, we demonstrate that HU-based PTPD is a species-specific hFEN1 inhibitor. In contrast, another reported hFEN1 inhibitor, the arylstibonic acid derivative NSC-13755, was determined to have off-target effects resulting in a synthetic lethal phenotype with y RAD27 -deficient strains. Our study expands the list of human–yeast complementation pairs to nonessential genes by defining novel cell-based assays that can be utilized as a broad resource to study human drug targets.